Measuring Mutual Fund Performance With Characteristic-Based Benchmarks. - Daniel, Kent (Journal of Finance, 1997)
This article develops and applies new measures of portfolio performance which use benchmarks based on the characteristics of stocks held by the portfolios that are evaluated. Specifically, the benchmarks are constructed from the returns of 125 passive portfolios that are matched with stocks held in the evaluated portfolio on the basis of the marked capitalization, book-to-market, and prior-year return characteristics of those stocks. Based on these benchmarks, 'Characteristic Timing' and 'Characteristic Selectivity' measures are developed that detect, respectively, whether portfolio managers successfully time their portfolio weightings on these characteristics and whether managers can select stocks that outperform the average stock having the same characteristics. The authors apply these measures to a new database of mutual fund holdings covering over 2500 equity funds from 1975 to 1994. Their results show that mutual funds, particularly aggressive-growth funds, exhibit some selectivity ability, but that funds exhibit no characteristic timing ability. Coauthors are Mark Grinblatt, Sheridan Titman, and Russ Wermers.